TINDAKAN RASIONAL KELAS MENENGAH PEKERJA MENGKONSUMSI KOPI DI STARBUCKS GRAHA PENA KOTA SURABAYA - Suhada, Husna (Paradigma, 2022)
This research is motivated by the trend of drinking coffee which has now become part of the lifestyle of modern society, the increase in coffee consumption in Indonesia is influenced by improving economic growth which has triggered the emergence of middle class people with diverse lifestyles, one of which is consuming coffee in modern coffee shops such as Starbucks Coffee. The reality shows that Starbucks visitors especially at the Graha Pena store in Surabaya, are mostly dominated by middle class status as workers, this is based on their need for a place to enjoy coffee, do work, tired release, socialize and hang out with colleagues,and also a place for meetings. This study aims to determine the rationality of middle class workers in consuming coffee at Starbucks Graha Pena, Surabaya City. This study uses the theory of social action initiated by Max Weber. This study uses a qualitative method with a case study approach. The data obtained were collected through observation, interviews and documentation. The results of this study show that all informants in this study are categorized as middle class workers who can be identified through education level, income, outcome, type of work, consumption pattern and lifestyle. There are three types of actions that influence the working middle class in deciding to consume coffee at Starbucks Graha Pena Surabaya city. The three types of action include instrumental rational action, value rational action, and the last is affective action.